Resident-City Identification: Translating the Customer Relationship Management Approach into Place Marketing Theory - Sebastian Zenker; Sibylle Petersen (European Regional Science Association (ERSA), 2010)
The aim of this paper is to determine why and under which condition residents enter into a strong and committed relationship with their place of living. We will present a model which outlines how cities could strengthen the resident-city identification by increasing the perceived place complexity. The model translates the Customer Relationship Management (CRM) approach of the general field of marketing (Customer-Company Identification) to the field of place marketing and combines it with theory development in Social Identity Theory and Theory of Organizational Identification. We hypothesize that a strong residents-city identification results from identity fit between the city prototype and the self-concept of the resident. The proposed model outlines the important role of the perceived place complexity as moderating variable. We propose that higher perceived complexity of a city allows for higher perceived fit between the self and the city, higher optimal distinctiveness, and higher perceived attractiveness of identification with the city. The question of how to increase identification with a place is crucial for place marketing and urban governance. Based on a review of existing research in social science we will outline the positive effects of identification on commitment, resilience towards negative information, selective information seeking and satisfaction. Practical implications for place marketers and potential for future empirical research are discussed.
Keywords: 330; Place Marketing; Resident-City Identification; Social Identity Theory; Place Prototype; Customer-Focused Marketing